2020
DOI: 10.24996/ijs.2020.61.11.17
|View full text |Cite
|
Sign up to set email alerts
|

Paleostress Analysis of the Northeastern Limb of Pulkhana Anticline /NE Iraq: Implications for Arabian Plate Tectonic Evolution

Abstract: Pulkhana anticline is located in Tuzhurmatu area, about 50 km SE of Kirkuk city. The study area forms a part of the Zagros Folded Zone which is situated in the unstable shelf of Iraq within the physiographic zone called Foothill Zone (in the middle of Hemrin- Makhul subzone). The north eastern limb of the anticline reaches to 50ᵒ and the dip of the  south western limb reaches to 70ᵒ. The core of the structure comprises the rocks of Fat’ha Formation surrounded by rocks of Injana and Mukdadiya Formations, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The morphotectonic features inferred from the analysis of the Shireen Anticline indicate that they are caused by the asymmetric movement on both sides of shallow structural faults in a northwest-southeast direction within the sedimentary cover (Ramthan et al, 2021), as well as variation of tectonic stresses is affecting the shape of the folds in northern Iraq (AL-Hachem, 2020). However, the previous studies concerning the analysis of tectonic stress indicated that the magnitude of the greatest compressive stress was in the direction of northeast-southwest and the perpendicularity of the greater tensile stress to it in the early stages of folding as a result of the oblique collision between the Arabian Plate and the Eurasian Plate, as well as the rotation of the Arabian Plate counterclockwise (Agard et al, 2005;Othman and Jadda, 2020). This results in a differential motion that can be theoretically illustrated by Fig.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The morphotectonic features inferred from the analysis of the Shireen Anticline indicate that they are caused by the asymmetric movement on both sides of shallow structural faults in a northwest-southeast direction within the sedimentary cover (Ramthan et al, 2021), as well as variation of tectonic stresses is affecting the shape of the folds in northern Iraq (AL-Hachem, 2020). However, the previous studies concerning the analysis of tectonic stress indicated that the magnitude of the greatest compressive stress was in the direction of northeast-southwest and the perpendicularity of the greater tensile stress to it in the early stages of folding as a result of the oblique collision between the Arabian Plate and the Eurasian Plate, as well as the rotation of the Arabian Plate counterclockwise (Agard et al, 2005;Othman and Jadda, 2020). This results in a differential motion that can be theoretically illustrated by Fig.…”
Section: Resultsmentioning
confidence: 90%
“…The current study involved extracting the morphotectonic features using the digital processing of Landsat image as well as the derivation of certain models from the DEM that covers the Shireen anticline. Because of the collision of the Arabian Plate with the Eurasian Plate (Numan, 2001;Agard et al, 2005;Othman and Jadda, 2020), the Shireen anticline showed certain morphotectonic properties due to the influence of different horizontal compressive stresses from the north and northeast. The results of the morphotectonic analysis revealed that there are several faults in the southwestern limb that have contributed to a clear displacement in the layers as well as an increase in the effect of tectonic uplift in this part of the anticline, which may have indicated that this limb has suffered extreme stresses relative to the northeastern limb.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation